Fetal Cerebral Ventricular Asymmetry Without Dilation: A Systematic Review - Sgayer, Inshirah; Khatib, Nizar; Lowenstein, Lior; Odeh, Marwan (Ultraschall in der Medizin - European Journal of Ultrasound, 2025)
The aim of this systematic review was to investigate the outcomes of pregnancies with fetal cerebral lateral ventricle asymmetry without dilation. We conducted a comprehensive literature search in the Embase, Medline, and Web of Science databases until April 29, 2024, of observational cohort studies that reported fetal ventricular asymmetry without dilation detected on ultrasound or magnetic resonance imaging. Of the 150 studies identified, 6 met the inclusion criteria. Among the cases of non-dilated ventricular asymmetry, 36.8–46.2% progressed to ventriculomegaly on follow-up by neurosonography or magnetic resonance imaging. Additional findings in the central nervous system were observed in 5.5–10.5% of cases, while 7.6% had additional fetal body findings. Abnormal genetic findings were present in 5.1% of cases. Postnatal follow-up indicated no abnormal developmental findings during the first year of life. By the age of 9–11 years, lower writing speed was observed, yet verbal fluency scores were higher than in the general population. In conclusion, non-dilated ventricular asymmetry in fetuses showed the potential for progression to ventriculomegaly, and linkage to genetic abnormalities. Larger prospective studies are essential to fully elucidate the condition’s natural history and refine clinical management strategies.
Keywords: fetal neurology; lateral ventricles; developmental outcome; asymmetry